The Influence of Market Orientation and Entrepreneurial Orientation to Competitive Advantage through Business Innovation: Study on Batik Trusmi Cirebon West Java Province Indonesia - Suharto, Suharto; Subagja, Iwan Kurniawan (International Review of Management and Marketing, 2018)
The advancement of the company in the batik industry is entirely dependent on the company’s ability to create and grow competitiveness that can adapt quickly to changes that occur. This study aims to analyze the influence of market orientation and entrepreneurship orientation to competitive advantage through business innovation. The research was conducted in Batik Trusmi Cirebon, West Java Province, Indonesia. The number of respondent as many as 168 respondents. The sampling technique using purposive sampling. The analysis tool was done using descriptive analysis and Structural Equation Modeling (SEM) version 22. The results show that market orientation and entrepreneurship orientation have a positive and significant impact on competitive advantage through business innovation. Keywords: market orientation, entrepreneurial orientation, competitive advantage and business innovation. JEL Classifications: M31, O